Design and application of a new adjustable pressure-reducing headband - LI, Xianwen; SUN, Xiumei; WANG, Chenlin (Chinese Journal of Integrative Nursing, 2024)
In order to fix the tissue structure and reduce infection after craniocerebral surgery, fixation headbands are usually worn. Suitable and flexible fixation head bands are essential to promote wound healing, reduce local bleeding, and reduce the occurrence of head pressure injuries. This study introduces the design and use of a new adjustable pressure-reducing headband, which can effectively improve the fixing effect, reduce the occurrence of pressure injury, reduce the work burden of medical staff, and increase the comfort of patients. (颅脑术后为了固定组织结构和降低感染, 患者通常会佩戴头部固定带。合适和灵活可调的头部固定带对于促进伤口愈合、减少局部出血、降低头部压力性损伤的风险至关重要。本研究介绍了一款实用新型可调节式减压头带的设计和使用方法, 其能够有效提高固定效果, 提升佩戴灵活性, 对降低压力性损伤风险、减轻医护人员工作负担和增加患者的舒适性有着积极作用。)